SATISFACTION FACTORS INFLUENCE ON THE PERFORMANCE OF EMPLOYEES WORKING CASSAVA PROCESSING COMPANY - Sukirman Sukirman Sukirman (STMIK Jakarta, 2004)
This study aims to determine the influence of factors affecting the level of job satisfaction asindependent variables are salary, kepemimpinandan attitude of co-workers to employeeperformance as the dependent variable. Kerterkaitan extent between independent variableswith dependent variable and significant or not from the day of testing of existing samples.From the test it was apparent factor of job satisfaction, pay, leadership and attitudes of peershas significant influence and positive impact on employee performance. Attitude is a factorco-workers who have the most dominant influence of other variables disbanding, co-workersattitudes can be explained variation in the performance of employees amounted to 99.5%while the remaining 0.5% is explained by other factors of job satisfaction.